Purification and properties of the Hpa I methylase. - Yoo, O J (1982)
The purification and catalytic properties of the homogeneous Hpa I methylase is described. The enzyme exists as a single polypeptide chain with a molecular weight of 37,000 +/- 2,000 was shown by sedimentation equilibrium and polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulfate. The Hpa I methylase transfers methyl groups of S-adenosylmethionine to adenine present in the recognition sequence d(G-T-T-A-A*-C), A* is the N6 methyl adenosine. An average of 2.1 methyl groups per recognition site are transferred by the Hpa I methylase.